SREB, a GATA transcription factor that directs disparate fates in Blastomyces dermatitidis including morphogenesis and siderophore biosynthesis. - Gregory M Gauthier; Thomas D Sullivan; Sergio S Gallardo; T Tristan Brandhorst; Amber J Vanden Wymelenberg; Christina A Cuomo; Garret Suen; Cameron R Currie; Bruce S Klein (PLoS Pathogens)
Blastomyces dermatitidis belongs to a group of human pathogenic fungi that exhibit thermal dimorphism. At 22 degrees C, these fungi grow as mold that produce conidia or infectious particles, whereas at 37 degrees C they convert to budding yeast. The ability to switch between these forms is essential for virulence in mammals and may enable these organisms to survive in the soil. To identify genes that regulate this phase transition, we used Agrobacterium tumefaciens to mutagenize B. dermatitidis conidia and screened transformants for defects in morphogenesis. We found that the GATA transcription factor SREB governs multiple fates in B. dermatitidis: phase transition from yeast to mold, cell growth at 22 degrees C, and biosynthesis of siderophores under iron-replete conditions. Insertional and null mutants fail to convert to mold, do not accumulate significant biomass at 22 degrees C, and are unable to suppress siderophore biosynthesis under iron-replete conditions. The defect in morphogenesis in the SREB mutant was independent of exogenous iron concentration, suggesting that SREB promotes the phase transition by altering the expression of genes that are unrelated to siderophore biosynthesis. Using bioinformatic and gene expression analyses, we identified candidate genes with upstream GATA sites whose expression is altered in the null mutant that may be direct or indirect targets of SREB and promote the phase transition. We conclude that SREB functions as a transcription factor that promotes morphogenesis and regulates siderophore biosynthesis. To our knowledge, this is the first gene identified that promotes the conversion from yeast to mold in the dimorphic fungi, and may shed light on environmental persistence of these pathogens.